2022
DOI: 10.3390/ijms232314847
|View full text |Cite
|
Sign up to set email alerts
|

Complete and Prolonged Inhibition of Herpes Simplex Virus Type 1 Infection In Vitro by CRISPR/Cas9 and CRISPR/CasX Systems

Abstract: Almost all people become infected with herpes viruses, including herpes simplex virus type 1 (HSV-1), during their lifetime. Typically, these viruses persist in a latent form that is resistant to all available antiviral medications. Under certain conditions, such as immunosuppression, the latent forms reactivate and cause disease. Moreover, strains of herpesviruses that are drug-resistant have rapidly emerged. Therefore, it is important to develop alternative methods capable of eradicating herpesvirus infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Numerous studies have already demonstrated the downregulation of viral infection in animal cell cultures. These studies have employed various types of Cas proteins depending on whether the targeted virus is based on DNA or RNA [ 91 , 92 ]. For example, CRISPR/Cas9 and Cas12a were shown to downregulate the infection of Green Monkey kidney cell culture by Herpes Simplex Virus 1 (HSV-1) [ 91 ].…”
Section: Crispr/cas-system As a Tool To Target Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have already demonstrated the downregulation of viral infection in animal cell cultures. These studies have employed various types of Cas proteins depending on whether the targeted virus is based on DNA or RNA [ 91 , 92 ]. For example, CRISPR/Cas9 and Cas12a were shown to downregulate the infection of Green Monkey kidney cell culture by Herpes Simplex Virus 1 (HSV-1) [ 91 ].…”
Section: Crispr/cas-system As a Tool To Target Virusesmentioning
confidence: 99%
“…These studies have employed various types of Cas proteins depending on whether the targeted virus is based on DNA or RNA [ 91 , 92 ]. For example, CRISPR/Cas9 and Cas12a were shown to downregulate the infection of Green Monkey kidney cell culture by Herpes Simplex Virus 1 (HSV-1) [ 91 ]. In this study, the authors targeted the HSV-1 genome with a Cas9 or Cas12a protein and a gRNA specific to a viral DNA polymerase and were able to see a clear diminution of the infection of the cell culture as well as an immunity that lasted for several days.…”
Section: Crispr/cas-system As a Tool To Target Virusesmentioning
confidence: 99%
“…Single-stranded RNA virus CRISPR/Cas9 system (K. Li et al, 2020) [67] Herpes Simplex Virus (HSV) Double-stranded DNA virus CRISPR/Cas9 system (Karpov et al, 2022) [59] Adeno-associated virus (AAV) Single-stranded DNA virus CRISPR/Cas9 with chemically modified sgRNA (Kim et al, 2021) [61]…”
Section: Retrovirusmentioning
confidence: 99%
“…15 Other researchers reinforce the importance of developing alternative methods for controlling these viruses and even capable of eradicating latent infections. 9,16, 17 Although current antivirals are still viable treatments for active herpetic diseases such as keratitis, controlling recurrence and the virus in the latent phase remains a challenge due to a virus in its latent state being resistant to all antiviral drugs. 14, [16][17][18] Vaccines targeting this viral group have not yet been developed, which increases the need for effective therapies that not only safely treat active herpesvirus infection, but also aim to prevent latent infection.…”
Section: No Outbreaksmentioning
confidence: 99%